Cistanche tubulosa Protects Dopaminergic Neurons through Regulation of Apoptosis and Glial Cell-Derived Neurotrophic Factor: in vivo and in vitro - Xu, Qian; Fan, Wen; Ye, Shui-Fen; Cong, Yi-Bo; Qin, Wei; Chen, Shi-Ya; Cai, Jing (Frontiers in Aging Neuroscience, 2016)
Parkinson’s disease (PD) is a neurodegenerative disease with the pathological hallmark of reduced nigrostriatal dopamine. In traditional Chinese medicine (TCM) clinical practice, the nanopowder of Cistanche tubulosa has therapeutic effects on PD. To identify the therapeutic mechanism, this study tested the protective effect of different doses of MPP+-induced toxicity in MES23.5 cells using the MTT assay and in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) -induced PD mice (vehicles). Immunohistochemistry was used to assess cytomorphology and tyrosine hydroxylase (TH) expression. Behavioural tests in vehicles, high performance liquid chromatography (HPLC) tests in dopamine, immunohistochemistry and western blot analysis were used to detect the expression of TH, glial cell line-derived neurotrophic factor (GDNF) and its receptors. Our results demonstrated that the C. tubulosa nanopowder improved the viability of MPP+-treated cells, increased TH expression and reduced the number of apoptotic cells. It also increased Bcl2 protein expression and suppressed Bax protein expression in MPP+-treated cells in a dose-dependent manner. In addition, C. tubulosa nanopowder improved the behavioural deficits in vehicle mice, reduced the stationary duration of swimming, enhanced the ability for spontaneous activity, and increased the expression of GDNF, the GDNF family receptor alpha (GFRα1) and Ret in cells of the substantia nigra (SN). Furthermore, the protein expression of GDNF, GFRα1 and Ret increased after treatment with different doses of C. tubulosa nanopowder, with a significant difference between the high-dose and vehicle groups. The protein expression of Bcl2 and Bax were similar in the in vivo and in vitro, which suggested that C. tubulosa nanopowder has anti-apoptotic effects in neurons.